Inflammatory Marker and their Association with COVID-19 Severity in Pregnant Women - Yuyun Lisnawati; Akbar Purnadiputra; Lucky Savitry Widyakusuma; Sri Pudyastuti; Amanda Mustika Sari (Indonesian Journal of Obstetrics and Gynecology, 2026)
Abstract : Objective: To analyze the correlation between blood markers; C-Reactive Protein (CRP), D-Dimer, Neutrophil-to-Lymphocyte Ratio (NLR) and the severity of COVID-19 in pregnant women during the 2020 pandemic at Persahabatan Hospital, Jakarta. Method :This cross-sectional study was conducted at Persahabatan Hospital, a National Respiratory Referral Center in Jakarta. A total of 525 pregnant women with confirmed COVID-19 who met the inclusion criteria were included in the study. Laboratory markers, including CRP, D-Dimer, and NLR, were analyzed and categorized as normal or elevated. Data were analyzed using the Chi-square test, and correlations were evaluated using Spearman’s rank correlation coefficient. Result :The results showed that elevated biomarkers were significantly correlated with increased disease severity. CRP (>10 mg/L), D-Dimer (>3333 mg/L), and NLR (?5.8) were all associated with moderate to severe disease. All biomarkers demonstrated a significant correlation with disease severity (p < 0.005). Conclusion: Elevated CRP, D-Dimer, and NLR levels are associated with increased disease severity in pregnant women with COVID-19, suggesting their potential role as practical indicators for disease severity assessment. Keywords : Covid 19, CRP, D-Dimer, NLR, Pregnant.